Development and Evaluation of High Bioavailable Sustained-Release Nimodipine Tablets Prepared with Monolithic Osmotic Pump Technology - Kong, Hua; Yu, Fanglin; Liu, Yan; Yang, Yang; Li, Mingyuan; Cheng, Xiaohui; Hu, Xiaoqin; Tang, Xuemei; Li, Zhiping; Mei, Xingguo (Current Drug Delivery, 2018)
Background: Frequent administration caused by short half-life and low bioavailability due to poor solubility and low dissolution rate limit the further application of poorly water-soluble nimodipine, although several new indications have been developed. To overcome these shortcomings, sophisticated technologies had to be used since the dose of nimodipine was not too low and the addition of solubilizers could not resolve the problem of poor release. Objective: The purpose of this study was to obtain sustained and complete release of nimodipine with a simple and easily industrialized technology. Methods: The expandable monolithic osmotic pump tablets containing nimodipine combined with poloxamer 188 and carboxymethylcellulose sodium were prepared. The factors affecting drug release including the amount of solubilizing agent, expanding agent, retarding agent in core tablet and porogenic agent in semipermeable film were optimized. The release behavior was investigated both in vitro and in beagle dogs. Results: It was proved that the anticipant release of nimodipine could be realized in vitro. The sustained and complete release of nimodipine was also realized in beagles because the mean residence time of nimodipine from the osmotic pump system was longer and Cmax was lower than those from the sustained-release tablets in market while there was no difference in AUC(0-t) of the monolithic osmotic pump tablets and the sustained release tablets in market. Conclusion: It was reasonable to believe that the sustained and complete release of poorly watersoluble nimodipine could be realized by using simple expandable monolithic osmotic pump technology combined with surfactant.
Keywords: nimodipine